PENGARUH PERENCANAAN SDM DAN KOMPETENSI KARYAWAN TERHADAP KINERJA KARYAWAN (DINAMIKA DOTCOM, 2016)
The purposes of this research are (1) to analyze whether Human Resource planning and competence simultaneously affect the performance of employees (2) for Human resource planning and competency as partial effect on employee performance. Based on the researchers previously, the first hypothesis is Human Resource planning and employee competency has simultaneous influence to employee performance proved to be true. This is indicated by F count 66.045 with a 0.000 probability of error of 5% (0,000 Sig) <Î± (0.05). Determination coefficient value (R Square) or R2 = 0.781 means that Human Resource planning and employee competencies has contribute to employee performance, amounted 0,781, or 78.10%. It is means that human resource planning and competency of employees has a significant influence to performance of the manager, amounted 78.10%, while the remaining 21.90% is the influence of other factors that were not studied. The second hypothesis which states that Human resource planning and employee competency as partial to performance of employees. Regression analysis showed that the variables of planning (X1) obtained t-count 11,345, because t-count > t table is 11.345> 1,98 therefore H0 refused and H1 accepted, meaning planning (X1) effect on employee performance variable (Y), while competence variable (X2) obtained t count 0.490, because t-count <t table is 0.490 <1,98 therefore H0 refused and H1 accepted, it means that competence variable has no effect to employee performance variable (Y).Â Keywords: Human Resource Planning, Competence Employees, Employee Performance